Concentration quenching dynamics in silica glass highly doped with Er3+ - Wörmann Tim J.; Brunzell Martin; Pasiskevicius Valdas; Maniewski Pawel (EPJ Web of Conferences)
In this study, quenching dynamics in RE-doped silica glass were investigated through the measurement of excited-state lifetimes of heavily doped silica micro-hemispheres fabricated directly on the end face of a multimode fiber (MMF).